Addition of Three Angelfish (Family: Pomacanthidae) to the Ichthyofauna of West Bengal, India - Ray, Dipanjan; Yennawar, Prasanna; Ghorai, Narayan; Mohapatra, Anil (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.